Assessment of subject-normalized comprehensiveness of research-intensive universities - Mendes, Saulo (Scientometrics, 2025)
Evaluation of university league tables is a controversial topic in higher education studies and metrics of scientific evaluation. Since its appearance on an international scale two decades ago, significant criticism of their methodologies has been accumulating without being addressed. One important bias regards the unequal distribution of research output and impact across different subjects, which in turn favors institutions that have the strongest performance in medical and physical sciences. The university league tables are revisited by normalizing each field to create a uniform distribution of value. Then, the overall performance of an institution is interpreted as the probability of having a high score in any given academic field while not inducing a zero-sum game . The present assessment shows that the main difference between hundreds of leading research universities is whether their coverage of all areas of human knowledge is comprehensive or specialized, whereas their mean performance per subject is nearly indistinguishable.